Identification of Digestive Tract Worms in Javan Gibbons (Hylobates moloch) at Maharani Zoo - Siagian, Tetty Barunawati; Pangestu, Arjun; Yuliati, Nani; Yudha, Yudha (Universitas Labuhanbatu, 2024)
Worm infections in Javan gibbons often do not cause clinical symptoms, but have an impact on the health and performance of Javan gibbons, so a fecal examination is needed to determine the presence of worm infections in Javan gibbons. The aim of this research is to identify digestive tract worms that infect Javan gibbons at Maharani Zoo. The research was conducted on 3 Javan gibbons consisting of 2 males and 1 female with an age range of 6-14 years and a body weight of 4-6 kg. Macroscopic identification of worms in Javan gibbons showed an abnormality in one of the Javan gibbon's feces. The feces abnormality is in the form of a very soft consistency, with a brownish yellow color, and the feces has a foul odor. Microscopic identification of worms in Javan gibbons showed positive results for the presence of eggs and larvae Strongyloides in one of the Javan gibbons. The Strongyloides worm larvae identified were rhabitiform. The cause of worm infections in Javan gibbons was due to the vegetable feed given, namely water spinach and mustard greens, being contaminated with Strongyloides worm eggs. Prevention needs to be done to prevent contamination of worm eggs, including washing the vegetables.